Assumptions and Processes for the Development of No-Notice Evacuation Scenarios for Transportation Simulations. Issue 1 (March 2013) - Murray-Tuite, Pamela; Wolshon, Brian
Emergency management agencies and departments of transportation benefit from transportation simulation support when developing their emergency response or evacuation plans. No-notice events are increasingly becoming part of these plans. Few, if any, studies have shown how to operationalize general no-notice evacuation considerations. To fill this gap, this article describes essential features and reasonable assumptions that should be considered in the development of no-notice evacuation scenarios for use in conjunction with transportation simulation models. Although the information presented here centers on a specific location and disaster, the concepts may be generalized and adapted for use in other locations and hazards and are of value to both practitioners as well as researchers seeking to develop similar models.